Self-evaluation of nurse profession perception and ability of emphatic understanding other people by nursery students - Krajewska-Kułak, Elżbieta; Damme-Ostapowicz, Katarzyna Van; Bielemuk, Agnieszka; Penar-Zadarko, Beata; Rozwadowska, Emilia; Lewko, Jolanta; Kowalewska, Beata; Kondzior, Dorota; Kowalczuk, Krystyna; Klimaszewska, Krystyna; Terlikowski, Robert (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. Professional activity of medical staff is connected with demonstrating the interest and compassion for suffering people and making an effort for helping them. Aim of the study. Our objective was to analyze nurses’ self-evaluation of their profession perception, reasons for choosing to study nursing, bachelor of nursing students’ emphatic abilities and to assess whether there is any difference in emphatic abilities depending on the year of study and the motivation underlying the choice of a nursing school. Material and methods. The study group included 237 bachelor of nursing students. Questionnaire consisted of a general part (6 questions) and a basic part (questionnaire of empathic understanding other people by Węglikowski) was used. Results. The students chose nursing faculty independently (51.9%), because they weren’t accepted for other faculties (27%), coaxed by friends or family (19.8%), expecting to find a job easily after graduation, felt pressed to continue a family tradition or wanted to attain higher education (1.6% each). In the opinion of the most respondents a nurse should be a person of vocation and patience, who wants to help people. For the most of respondents nurse’s work was involved with being needed (75.9%), with being close to suffering patients (64.1%) and with kindness (59.9%). In the majority of opinions a nurse should be a thorough, conscientious, disciplined and empathic person. The third-year nurses had the highest empathy scores (70.5 ± 8.3). The differences were statistically significant between particular years of study. Significant differences in empathy scores were detected between students who chose their faculty independently and those who studied nursing because they weren’t accepted for other faculties (p < 0.01) and between students, who chose bachelor of nursing program as a result of coaxing by a friend or a family. Conclusions. The majority of students chose nursing faculty independently. The most respondents said that a nurse should be a person of vocation. In majority of opinions a nurse should be conscientious, thorough, disciplined and empathic. The highest empathy scores had the third-year students and those, who chose the nursing faculty independently. Nursing Topics 2010; 1 (1): 1-10